UNATTENDED VERSUS OFFICE, AMBULATORY AND CENTRAL BLOOD PRESSURE MEASUREMENTS IN HYPERTENSIVE AND DIABETIC PATIENTS. (June 2018) - Polonia, J.; Abreu, S.; Baptista, C.; Silva, J.; Barbosa, L.
Abstract : Objective: To compare unattended blood pressure (BP) data with casual, 24-ambulatory and central measurements in hypertensive patients with and without diabetes Design and method: In the same hypertension clinic we evaluate 130 consecutive hypertensive patients (HTs, 56% female, 59+16 yrs, BMI 28+5 Kg/m2) and 96 hypertensive diabetics (DMs, 62% female, 64+9 yrs, BMI 29 ± 5 Kg/m2) who were referred to perform a 24-h ambulatory BP and who within the interval of 48 hours were underwent casual BP (average of 3 recordings) to an unattended 3 BP measurements separated by 2 minutes with a pre-programmed Omron M10-IT and to the evaluation of central BP from the aortic wave form (SpygmoCor). Figure. No caption available. Results: Table shows that in both HTs and DMs unattended BP was significantly lower than casual BP although less pronounced in DMs. Average of anti-hypertensive drugs were 2.7+0.6 in HTs and 3.2+0.7 in DMs. In both groups the difference persisted along the terciles of distribution of unattended systolic BP values. Unattended SBP values were similar to ambulatory BP values (to 24 h SBP in HTs and daytime BP in DMs). Conclusions: In HTs with and without DM the unattended BP measurement significantly underestimates by SBP 12–17; DBP 3–6 mm Hg the BP measured in office, being more close to ambulatory BP values. That difference should be taken into account since targets based on these measurements are not equivalent.